HUBUNGAN ANTARA KREATIVITAS DALAM MENGOLAH SUMBER DAYA PERIKANAN LAUT DENGAN PEMENUHAN KEBUTUHAN DASAR PEREMPUAN PESISIR DI DESA BUNGKO LOR KABUPATEN CIREBON, JAWA BARAT - Friska Febriani; Yuce Sariningsih (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2022)
Creativity is the potential of all people who do not need special talents and abilities, generally people actually lose creativity because of the cultivation process including formal education that promotes creativity and provides a gap in society that only educated people can be seen, listened to and respected, this is the same thing that makes coastal communities rarely seen. And the processing of marine fishery resources is a form of embodiment of creativity, this research was raised with the title "The relationship between creativity in processing marine fishery resources and the fulfillment of the basic needs of coastal women". The purpose of this study is to analyze and describe how the creativity of coastal women in processing marine fishery resources, to analyze and describe how the basic needs of coastal women are, to analyze and describe how the relationship between creativity in processing marine fishery resources and the fulfillment of the basic needs of coastal women in bunko lor village, Cirebon regency. The methods used are quantitative approaches with descriptive analysis, data collection techniques, namely by non-participant observations, literature studies and filling out questionnaires, the population in this study is coastal women in bunko lor village who have a fishery processing business totaling 30 respondents. The sampling technique uses probability sampling, Area random sampling type. For analysis techniques and hypothesis testing using spearman rank correlation test. The results showed that there was no significant relationship between creativity in processing marine fishery resources and meeting the basic needs of coastal women in Bungko Lor Village, Cirebon Regency.